Enhancing the Dispatchability of Variable Wind Generation by Coordination With Pumped-Storage Hydro Units in Stochastic Power Systems - Khodayar, Mohammad E.; Shahidehpour, Mohammad; Lei Wu (IEEE transactions on power systems, 2013)
The ever-increasing penetration of variable wind energy in power systems affects the hourly dispatch of thermal power generation in electricity markets. The variability of wind energy, which makes the wind energy non-dispatchable and difficult to control, could bring significant challenges to power system operators. The hourly coordination of wind power generation units with pumped-storage hydro (PS) generation could relieve the variability of wind energy and increase its dispatchability. The wind-PS coordination is based on the application of stochastic security-constrained unit commitment (stochastic SCUC). In this study, the coordinated hourly bus-level scheduling of wind-PS is compared with the coordinated system-level operation strategies in the day-ahead scheduling of power systems.